Chronopharmaceuticals In Nocturnal Asthma- A Review - Panwar, Aakash S (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTDue to advances in chronopharmaceuticals, the traditional goal of pharmaceutics (like drug delivery systems with a constant drug release rate) is becoming obsolete. The major bottleneck in the development of drug delivery systems that match the circadian rhythm may be the availability of appropriate technology. Until now, the emphasis has been on formulations that maintain constant drug levels throughout the day. But we now need to develop more biologically appropriate formulations that take account of variations in bodily functions, such as blood pressure, asthma, arthritis, duodenal ulcer, cancer, diabetes, hypercholesterolaemia and some neurological disorders during the day. In asthma, a drug that could address the progressive increase in airway resistance during the night could offer better symptom control in the early morning hours. In chronopharmacotherapy drug administration is synchronized with circadian rhythms. If the peak of symptoms occurs at daytime a conventional dosage form can be administrated just before the symptoms are worsening. If symptoms of the disease became worse during the night or in the early morning the timing of drug administration and nature of the drug delivery system need careful consideration.